Riko the series (murrotal edition): Surah At-Tin episode as a medium to introduce surah At-Tin to children - Fatimah Azzahro; Hartini Salama (LADU: Journal of Languages and Education, 2022)
Background: Quran's introduction to children has evolved over time. Animation can now be a medium to learn the Quran such as "Riko the Series: Murrotal Edition” which introduces the Quran to children. Purpose: The aim of this research is limited to how the visualizations constructions of “Riko the Series: Murrotal Edition" in the Surah At-Tin episode introduce Surah At-Tin to the children. Design and Methods: This research uses a descriptive qualitative method with the video of Surah At-Tin’s episode from “Riko the Series: Murrotal Edition" as the source of the data. Due to the fact, that the research study is limited to the visualization of the episode, the theories that are used as tools in analyzing the data are the theory of Semiotic Significations. Result: Visual significations are divided into six (6) structures, they are (1) the opening of the video; (2) the section header; (3) the opening of the surah; (4) the visualization during the recitation of the surah; (5) the second reading section; (5) the third reading section. There are two forms of visual patterns found in the video (episode), they are: (1) the visualization related to verses 1 and 2 of surah At-Tin; (2) the visualization narratives which have no specific form in relation to verses 3 until 8 of Surah At-Tin. The video applies repetition (three times) to introduce and familiarize Surah At-Tin. The solid visual signification construction serves as a medium to introduce Surah At-Tin to children. Keywords: Quran, Murrotal, Riko the Series, Islamic Education, Signification Theory.